2001
DOI: 10.1111/j.1834-7819.2001.tb00268.x
|View full text |Cite
|
Sign up to set email alerts
|

The increasing problem of hepatitis C virus infection

Abstract: The widespread incidence of hepatitis C (HCV) infection throughout the community is of concern. Although many of those infected will not suffer significantly from their infection, up to one-third will have liver disease, fatigue and oral health problems. General dental practitioners need to be aware of the precautions necessary in treating people with severe liver disease. This paper discusses the issues associated with treating patients who have HCV infection including the importance of preventive programs to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…Poor oral health has been reported in HCV-infected patients [33][34][35][36]. Coates et al reported that the experience of dental caries was significantly worse in HCVinfected subjects than in patients in general [33].…”
Section: Discussionmentioning
confidence: 99%
“…Poor oral health has been reported in HCV-infected patients [33][34][35][36]. Coates et al reported that the experience of dental caries was significantly worse in HCVinfected subjects than in patients in general [33].…”
Section: Discussionmentioning
confidence: 99%
“…Some patients had decreased sensitivity of taste despite the fact that they were unaware of their taste disorder. In addition, poor oral health has been reported for HCV-infected patients [16][17][18][19]. In our previous study, dental problems delayed the initiation of IFN therapy for a maximum of 105 days [7].…”
Section: Discussionmentioning
confidence: 91%
“…probable increased risk of developing periodontal disease associated with a diabetes-induced inflammatory response) or indirectly (probable increased risk of dental caries in HCV-infected patients by decreased salivary flow due to prescribed medications). [2223]…”
Section: Oral Healthmentioning
confidence: 99%